Trade Diversion under Selective Preferential Market Access - Borchert, Ingo (2012)
The European Community (EC) operates a multi-layered GSP scheme in which different groups of developing countries are granted varying degrees of market access. This paper analyzes the question of trade diversion among different categories of beneficiary countries ensuing from the selectivity of preferential market access. Evidence from a disaggregated panel data analysis reveals sizable intra-developing country trade diversion. The losses for relatively disadvantaged countries in terms of forgone trade volume are estimated to range between about 2% to 20% of their total trade with the EC. The distortions are driven by highly substitutable, mostly labour-intensive commodities.